(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to clarifying the current state of legal regulation governing the implementation of state policy in relation to the development and functioning of the virtual asset market in the United States. At present, the principal legal instruments regulating this sector are the Internal Revenue Code and the Infrastructure Investment and Jobs Act of 2021 (formally: An Act to Authorize Funds for Federal-Aid Highways, Highway Safety Programmes, and Transit Programmes, and for Other Purposes). These legislative instruments form the basis upon which United States public administration bodies interpret cryptocurrencies and other virtual assets not as legal tender, but as property – that is, as electronically stored assets which may be acquired, disposed of, owned, transferred, and exchanged. Nonetheless, as of late April 2025, the United States lacks a comprehensive federal statutory framework that governs the legal status of non-fungible tokens (NFTs), decentralised finance (DeFi) platforms, and stablecoins. This regulatory lacuna persists despite a clear demonstration of political will at the executive level, most notably articulated in Executive Order 14178 of 23 January 2025, which outlines the President’s commitment to the development of a unified policy approach to virtual assets. However, no draft federal law has yet been introduced that would offer a consolidated legal definition of virtual assets – including their classification and typology – the legal foundations for the operation and evolution of the virtual asset market, or the delineation of powers between federal and state regulators tasked with enforcing public policy in this domain. At the time of writing, two federal bills (the GENIUS Act and the STABLE Act) are under consideration in the United States Congress. These legislative proposals focus on the regulation and oversight of stablecoin- related transactions and operations. Nevertheless, they fall short of resolving the broader problems of legal uncertainty regarding both the overarching legal regime applicable to the virtual asset market and the regulatory treatment of stablecoins in particular. In this regard, it is concluded that, to date, the future trajectory of legal reform intended to ensure the implementation of state policy on the development and regulation of the virtual asset market in the United States remains poorly defined and institutionally fragmented.